"Elephant trunk" and endovascular stentgrafting--a hybrid approach to the treatment of extensive thoracic aortic aneurysm - Holubec, Tomáš; Raupach, Jan; Dominik, Jan; Vojáček, Jan (Acta Medica, 2013)
A hybrid approach to elephant trunk technique for treatment of thoracic aortic aneurysms combines a conventional surgical and endovascular therapy. Compared to surgery alone, there is a presumption that mortality and morbidity is reduced. We present a case report of a 42-year-old man with a giant aneurysm of the entire thoracic aorta, significant aortic and tricuspid regurgitation and ventricular septum defect. The patient underwent multiple consecutive operations and interventions having, among others, finally replaced the entire thoracic aorta with the use of the hybrid elephant trunk technique.
Keywords: dospělí; aneurysma hrudní aorty; Aortic Aneurysm, Thoracic; Endovascular Procedures; lidé; mužské pohlaví; Blood Vessel Prosthesis Implantation; Male; Stents; endovaskulární výkony; Adult; cévy - implantace protéz; stenty; Humans